Studying the acoustic emission of the temporomandibular joint - LIS, W.; SALAMON, R.; ZIENKIEWICZ, J. (Archives of Acoustics, 1999)
The method of acoustic emission is widely used for testing the strength of materials and in passive underwater acoustics. Recently in the field of medicine, acoustic emission signals received in the traditional phonendoscope method are recorded and processed using advanced electronic technology. Presented in this paper is an example of this work. It is a system that tests the acoustic emission of the temporomandibular joint which when in a pathological state seriously impairs important physiological functions of man. The presented system receives and records acoustic signals emitted by the joint. This is synchronised with the registration of the jaw displacement. Based on that, parameters and characteristics of acoustic emission signals which could indicate a specific disease of the joint are determined. In the research to date the focus has been on determining the statistical distributions of root-mean-square and maximal values of the signals and the current spectrums linked to the movement of the mandible. Clinical tests carried out at the Clinic of Maxillofacial Surgery at the Medical Academy of Gdańsk have provided preliminary confirmation of the usefulness of the system for diagnostic functions. The tests are being continued and are systematically contributing to the collection of signals and cases. This in turn is the condition of progress of continued work on the use of acoustic emission in diagnosing the temporomandibular joint.